Facile preparation of a polymer-ZnO composite colloid as an electron transport layer and its effects on inverted polymer solar cells. (October 2020) - Yi, Mo-Beom; Ku, Ja Ram; Yoon, Jin Soo; Kal, Jinha; Lee, Wonhee; Oh, Seong-Geun
Abstract: A polymer-ZnO colloidal solution was prepared as the organic-inorganic composite electron transport layer of inverted polymer solar cells (i-PSCs) by successive modification of ZnO particles with organic dispersant and polyethyleneimine (PEI), which offers an alternative to previously used complicated processes such as high temperature annealing or multi-layer coatings. The modification of ZnO surfaces with 2-(2-methoxyethoxy) acetic acid (MEA) provides colloidal stability and prevents aggregation of ZnO particles after adding PEI into the ZnO colloidal solution. The amount of incorporated PEI was increased to ~10 wt%, and the cell performance parameters of Jsc and fill factor (FF) were enhanced proportional to PEI content because of its contribution in decreasing the work function of ZnO ETL. By fabrication of i-PSCs with the modified ZnO ETL, the power conversion efficiency (PCE) was increased by ~40% from 5.10% to 7.51% in the ITO/ETL/PV-D4610:PC60 BM/MoO3 /Ag structure. The multi-functionalized ZnO ETL provides a more facile process for preparation of an organic-inorganic composite ETL to improve the performance of i-PSCs. Graphical abstract: Image 1 Highlights: Stable PEI-ZnO composite colloidal solution was prepared for electron transport layer in polymer solar cell. Successive surface modification of ZnO with MEA and PEI yielded stable composite colloid. The 40% of enhancement in PCE was obtained by using composite colloid.